Studies on sustained release platforms for delivery of therapeutic agents to the posterior segment of the eye - Joseph, Rini Rachel (2017)
For treatment of several disorders of the retinal area, the drug molecules need to be directly delivered to the posterior segment of the eye. The intravitreal route of drug delivery is the most common and effective route for delivering therapeutic amounts of drug to this area. However, the invasive nature of this route may cause several side effects. Trans-scleral route of ocular drug administration is a less invasive method, which may be used as an alternative route of drug delivery to target the posterior segment. Limitations of this route lie mainly in maintaining the required dose at the site of action, as well as overcoming several barriers (cell and systemic) to drug transport. Age Related Macular degeneration (AMD) is a disease of the posterior segment currently treated with monthly intravitreal injections of Anti-VEGF antibody, which are costly and invasive. Encapsulating drugs in carriers, such as liposomes has the potential to sustain the duration of drug release and increase the bioavailability of the drugs at the site of action thus reducing the need for frequent drug administration. In this work, the focus was on understanding the mechanisms of transport, controlling and optimizing the various factors that affect the encapsulation and delivery of drugs and nanocarriers trans-sclerally using ex vivo models. The effect of the various properties of the nanocarriers on scleral distribution and transport were evaluated in this work. An ex vivo setup was designed and optimized for use in trans-scleral transport studies. Porcine scleral tissues were used as the animal tissue model for the ex vivo studies performed. Various nanocarriers with different properties were explored for their trans-scleral transport using the ex vivo setup. In particular, liposomes were studied for their size, charge and rigidity. Lucentis loaded liposomes were then studied for trans-scleral transport and distribution of the drug from the liposomal formulations. The results obtained from these studies suggest that size, charge and flexibility of the liposomes determine their transport and scleral distribution properties. Smaller sized liposomes demonstrated higher intrascleral penetration compared to larger sized liposomes. Positively charged liposomes were found to be episclerally localized, compared to neutral or negatively charged liposomes. Liposomes made of unsaturated lipids such as POPC, with a lower melting transition temperature demonstrated higher intrascleral diffusion compared to liposomes made of saturated lipids such as DPPC. Rigid PLGA nanocarriers were also found to be episclerally localized rather than diffuse intrasclerally. Trans-scleral transport of Lucentis from different liposome-encapsulated formulations was compared with trans-scleral transport of bare-Lucentis and found to be slowed down in the case of encapsulated formulations. Negatively charged liposomes consisting of DPPC-DPPG demonstrated the highest encapsulation efficiency as well as the slowest ex vivo transscleral transport of the encapsulated Lucentis, over the study period of 7-days. The carriers maybe considered to be acting as episcleral or intrascleral depots and releasing the encapsulated drug, which then diffuses trans-sclerally. In conclusion, we have demonstrated the ability of nanocarriers of different properties to act as subconjunctival depot systems and providing sustained release. The findings from this work can be useful in developing successful sustained release therapeutics for diseases of the posterior ocular segment, and in particular, AMD.